ANALYSIS OF THE IMPLEMENTATION OF THE PRINCIPAL'S TRANSFORMATIONAL LEADERSHIP IN IMPROVING EDUCATIONAL QUALITY AT SMP NEGERI 2 PABELAN - Azyan Denis Syuhada; Nina Oktarina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Educational quality is a key indicator of the success of educational management and is influenced by various factors, one of which is the principal's leadership. Transformational leadership is considered an effective approach because it inspires, motivates, encourages innovation, and fosters the commitment of all school members to achieving shared goals. SMP Negeri 2 Pabelan was selected as the research site due to its Excellent accreditation and its continuous implementation of educational quality improvement programs. This study aims to analyze the implementation of the principal's transformational leadership style in improving educational quality at SMP Negeri 2 Pabelan, particularly in developing quality standards and transforming the school culture. The study employed a qualitative descriptive approach. Data were collected through observations, in-depth interviews, and documentation involving the principal, teachers, educational staff, and supporting documents. Data validity was ensured through source and technique triangulation, while data analysis followed the Miles, Huberman, and Saldaña model, including data reduction, data display, and conclusion drawing. The findings indicate that the principal has effectively implemented the four dimensions of transformational leadership: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. These dimensions were reflected in the formulation of a quality-oriented school vision and mission, participatory school program development, continuous academic supervision, teacher professional development, motivation and appreciation for teachers and staff, and the strengthening of a collaborative, disciplined, and innovative work culture. Furthermore, the principal fostered open communication, increased stakeholder participation, and established a quality culture that supports effective learning.